COVID-19 Vaccine-Associated Transient Global Amnesia: A Disproportionality Analysis of the WHO Safety Database - Merino, Diane; Gérard, Alexandre O.; Van Obberghen, Elise K.; Ben Othman, Nouha; Ettore, Eric; Giordana, Bruno; Viard, Delphine; Rocher, Fanny; Destere, Alexandre; Benoit, Michel; Drici, Milou-Daniel (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) spread rapidly, resulting in a global pandemic for which vaccines were quickly developed. As their safety continues to be monitored, cases of transient global amnesia (TGA) following mRNA vaccination with elasomeran have been reported. TGA is characterized by sudden onset of anterograde amnesia with preservation of other cognitive functions and resolution within 24 hours. We aimed to investigate the potential link of TGA with COVID-19 vaccines. We queried the World Health Organization VigiBase® for all reports of “Transient global amnesia”, up to December 6, 2021. Disproportionality analysis relied on the Reporting Odds Ratio (ROR) with its 95% Confidence Interval (CI) and the Information Component (IC). A positive lower end of the 95% CI of the IC (IC025) is used to statistically detect a signal. Of all TGA cases, 289 were associated with a COVID-19 vaccine, representing the most frequent association. Tozinameran was mostly represented (147, 50.8%), followed by AZD1222 (69, 23,8%), elasomeran (60, 20.8%), and JNJ-78436735 (12, 4.2%). With an IC025>0, COVID-19 vaccines showed a significant ROR (5.1; 95%CI 4.4-6.0). Tozinameran reached the strongest ROR (4.6; 95%CI 3.9-5.0), followed by elasomeran (4.4; 95%CI 3.4-6.0), AZD1222 (3.8; 95%CI 3.0-5.0), and JNJ-78436735 (3.7; 95%CI 2.1-6.0). Our analysis of COVID-19 vaccines-related TGA reports shows significant disproportionality. Cerebrovascular, inflammatory, or migrainous mechanisms may underlie this association. Yet, numerous confounding factors cannot be tackled with this approach, and causality cannot be ascertained. The identification of this trigger of TGA may help the clinician in his etiological research.